Positioning strategic competitiveness of green business innovation capabilities using hybrid method - Lin, Yuanhsu (Animo Repository, 2011)
There are intensive studies on the issues of environment practice and business innovation capability, have been dealt with extensively from practitioners and academicians, however, studies on the evaluation of green business innovation capabilities (GBICs) are few. This study tackles the evaluation assessment using fuzzy set theory, analytical network process and importance-performance analysis. Specifically, this study is using the theoretical framework of GBICs and proposed hybrid approach, which are new in the theoretical and empirical literatures. An expert group was empirical assessment to the perception on PWB sector and a manufacturing firm is evaluated. The analytical results indicated that this proposed hybrid method is a suitable and effective method for identifying and analyzing the strategic competitiveness of GBICs at case firm, especially when evaluation criteria are dependent in uncertainty. © 2010 Elsevier Ltd. All rights reserved.